Differentiation and Application of Human Pluripotent Stem Cells Derived Cardiovascular Cells for Treatment of Heart Diseases: Promises and Challenges - Gao, Yu; Pu, Jun (Frontiers in Cell and Developmental Biology, 2021)
Human pluripotent stem cells (hPSCs) are either derived from human embryos (human embryonic stem cells, hESCs) or reprogrammed from human somatic cells (human induced pluripotent stem cells, hiPSCs). They can potentially differentiate into all cell types found in human body. Precisely and spatiotemporally activate or inhibit various pathways of hPSCs have been shown to achieve high differentiation efficiency into cardiovascular lineages. In this concise review, we summarize and discuss the current differentiation protocols of hPSCs into cardiovascular cells and their therapeutic application for treatment of heart diseases in large animal models for a better application of hPSC derived cardiovascular cells in clinic.